Beyond the Flames: Firefighters as Humanistic Heroes in the Web Series Era - Hafizd, Ikhlassul; Lobodally, Altobeli (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2025)
A web series is an episodic video presentation available on the internet. One of the web series is The First Responder, which depicts the identity of the firefighter As the cultural industry, the web series convey the essential function of media and industry interests, which can bias the representation of reality in the firefighting profession. This study aims to explore the portrayal of the firefighter profession in the web series The First Responder and the motivations behind this representation. To answer this, it uses the representation theory with Roland Barthes' Semiotic Analysis method, which involves three analytical elements: denotation, connotation, and myth. This study found that there has been a reduction in the meaning of the firefighting profession. The First Responder web series has shifted the myth of the firefighting profession. The firefighting profession, which was previously viewed as a demanding and high-risk profession, has evolved, shifting towards heroes with a humanitarian spirit. This shift is the response to the market demands for increased public access to First Responders.